MUSE MUltipoint SErverless videoconferencing for interactive learning support - Montes, Isabel A.
Multipoint videoconferencing (MPVC) can be a powerful and effective tool in addressing the shortage of qualified teachers in rural communities. Given that IT infrastructure and expert personnel may be scarce in rural areas, a videoconferencing solution deployed for this environment should not depend on centralized servers and managers. Unfortunately, existing serverless MPVC systems have not yet been studied and optimized enough for serverless MPVC to be put to practical use. This project sought to develop an MPVC architecture with minimal requirements on the bandwidth and computing power of the end systems involved in a videoconference, in order to make it appropriate for the rural setting. The objectives of this work were to implement and compare the performance of different end system multicast architectures in a serverless MPVC system, consider and evaluate different P2P algorithms for serverless MPVC, and implement and evaluate a hybrid architecture of end system multicast and P2P principles. MUSE was developed as a proof-of-concept prototype for a minimum-requirement and serverless MPVC solution. It was designed such that the user could choose what scheme to use for sending its video streams throughout the network. MUSE can currently perform multiple unicast and application-layer multicast. It employs application-layer multicast according to the Narada protocol, adapted to fit the behavior of MPVC and combined with other performance-optimizing features. Small videoconferences with up to four members were successfully conducted on MUSE. Conferencing was done on both completely wired LAN setups, as well as mixed setups of wired and wireless connections to the LAN. These conferences were conducted among machines in a single room. Pilot testing was conducted with machines located in two different buildings in the university campus. Quality of services performance parameters were observed and measured during these tests. The application runs even without specific hardware requirements, although on slower or lower capability processors, the CPU usage could stay at around 100% throughout the duration of the videoconference. The quality of MUSE's videos are good enough for practical videoconferencing--videos can suffer choppiness from time to time, but for much of the time the videos are continuous and understandable. All in all, the performance of MUSE is sufficient for actual MPVC.